Research on The Construction of Community Workers Team in The New Era - Yang, Hao (Transactions on Economics, Business and Management Research, 2024)
At present, with the continuous advancement and development of smart cities, driven by the reform of network information technology and the rapid development of intelligent devices, community construction in the new era has become an indispensable part of urban construction, and community governance and services are playing an increasingly important role. The community is the smallest cell of the city. Improving community services is of great significance to grassroots governance. If there are problems with the community team itself, good social governance cannot be carried out. The current imbalance in the structure of the community worker team cannot meet the needs of residents, resulting in difficulties for community workers in carrying out certain specific work. This article analyzes the causes of the problem from three aspects: the structure, management, and work of the new era community team. By drawing on the advanced experience of community work construction at home and abroad, it puts forward suggestions from the aspects of enhancing the enthusiasm of community members, improving the conditions of the community team, and innovating the system and mechanism of the community team.